Readability assessment of Nigerian company income tax act - Musa Sulaiman Umar; Natrah Saad (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study was undertaken to examine the readability of the Nigerian Company Income Tax Act 2007 (CITA 2007), which is the main reference for taxpayers who have intention to comply. For that purpose, the researchers employed readability formulae namely Flesch Reading Ease Score (FRES), Flesch-Kincaid Grade Level (F-KGL), Average Sentence Length (ASL) and Percentage of Passive Voice (PPV). FRES measures the readability of technical writing and rates texts on a 0-100-point scale, while F-KGL translates the 0-100 raw FRES into the number of years of education generally required to understand the materials. On the other hand, ASL and PPV deal with average length and percentage of passive voice, respectively. All these measures were calculated using Microsoft Word 2000. The study found that CITA 2007 has low level of readability which made the Act very difficult to understand. Further, the results indicate that CITA 2007 can only be understood by those with tertiary education. The study recommends that tax simplification policy in Nigeria should include language simplification to enable taxpayers to understand the Act correctly which subsequently motivate them to comply voluntarily; and consequently result in more tax revenue to boost the economy of the nation.